Correction of Defective Protein Kinesis of Human P-glycoprotein Mutants by Substrates and Modulators - Tip W. Loo; David M. Clarke (1997)
There is growing evidence that abnormal protein folding or trafficking (protein kinesis) leads to diseases. We have used P-glycoprotein as a model protein to develop strategies to overcome defects in protein kinesis. Misprocessed mutants of the human P-glycoprotein are retained in the endoplasmic reticulum as core-glycosylated biosynthetic intermediates and rapidly degraded. Synthesis of the mutant proteins in the presence of drug substrates or modulators such as capsaicin, cyclosporin, vinblastine, or verapamil, however, resulted in the appearance of a fully glycosylated and functional protein at the cell surface. These effects were dose-dependent and occurred within a few hours after the addition of substrate. The ability to facilitate processing of the misfolded mutants appeared to be independent of the cell lines used and location of the mutation. P-glycoproteins with mutations in transmembrane segments, extracellular or cytoplasmic loops, the nucleotide-binding domains, or the linker region were processed to the fully mature form in the presence of these substrates. These drug substrates or modulators acted as specific chemical chaperones for P-glycoprotein because they were ineffective on the ∆F508 mutant of cystic fibrosis transmembrane conductance regulator. Therefore, one possible strategy to prevent protein misfolding is to carry out synthesis in the presence of specific substrates or modulators of the protein. There is growing evidence that abnormal protein folding or trafficking (protein kinesis) leads to diseases. We have used P-glycoprotein as a model protein to develop strategies to overcome defects in protein kinesis. Misprocessed mutants of the human P-glycoprotein are retained in the endoplasmic reticulum as core-glycosylated biosynthetic intermediates and rapidly degraded. Synthesis of the mutant proteins in the presence of drug substrates or modulators such as capsaicin, cyclosporin, vinblastine, or verapamil, however, resulted in the appearance of a fully glycosylated and functional protein at the cell surface. These effects were dose-dependent and occurred within a few hours after the addition of substrate. The ability to facilitate processing of the misfolded mutants appeared to be independent of the cell lines used and location of the mutation. P-glycoproteins with mutations in transmembrane segments, extracellular or cytoplasmic loops, the nucleotide-binding domains, or the linker region were processed to the fully mature form in the presence of these substrates. These drug substrates or modulators acted as specific chemical chaperones for P-glycoprotein because they were ineffective on the ∆F508 mutant of cystic fibrosis transmembrane conductance regulator. Therefore, one possible strategy to prevent protein misfolding is to carry out synthesis in the presence of specific substrates or modulators of the protein.